Farmasi dan Teori Konstitusi Nusantara: Apoteker sebagai Penjaga Keseimbangan Etis dan Hukum Lokal - Sudrajat, Hendra; Dita, Rahma (Jurnal Medika Farmaka, 2025)
This study examines the strategic role of pharmacists as ethical and legal mediators in Indonesia's pluralistic legal system. Based on the Nusantara Constitution theory, pharmacists are viewed not only as healthcare professionals but also as maintainers of the balance between state law and customary law. The research method uses a qualitative, normative-juridical approach with an interdisciplinary analysis of pharmaceutical science, constitutional law, and medical anthropology. Data were obtained through literature studies and case observations from indigenous communities in Papua, Kalimantan, and Nusa Tenggara. The results of this study indicate that pharmacists in indigenous areas face overlapping norms between professional codes of ethics, state law, and customary law. Their role as intermediaries enables culturally sensitive communication, the safe use of traditional medicines, and pharmaceutical practices based on local values. Pharmacists thus serve as a bridge between formal healthcare services and regional perspectives. This study recommends integrating local legal and cultural insights into pharmacy curricula and national policies to strengthen collaboration with customary authorities and build an inclusive, locally rooted health system.